2020
DOI: 10.5114/aoms.2020.91291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immunisation against PCSK9 in mice bearing melanoma

Abstract: Introduction: Inhibition of proprotein convertase subtilisin/kexin 9 (PCSK9) is an established modality for the treatment of hypercholesterolaemia. However, the impact of PCSK9 inhibition in other situations such as cancer remains largely unknown. The current study was conducted to study the effects of PCSK9 inhibition on cancer endpoints in mice bearing melanoma. Material and methods: To generate antiPCSK9 antibody in vivo, a nanoliposomal antiPCSK9 vaccine adsorbed to 0.4% Alum adjuvant was subcutaneously in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…14 Over the past 10 years, a considerable amount of literature has accumulated on the role of PCSK9 in hypercholesterolemia and human malignancies. 35,36 Recently, researchers have begun to assess anti-PCSK9 vaccines against breast cancer and melanoma in mice, 34,37 and a previous study reported that a nano liposomal anti-PCSK9 vaccine has potential anti-tumor effect in colorectal cancer. 14 This study directly linked PCSK9 with the development and progression of mouse adenomas and adenocarcinomas in transgenic mice, supporting previous studies which examined an anti-PCSK9 vaccine against colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Over the past 10 years, a considerable amount of literature has accumulated on the role of PCSK9 in hypercholesterolemia and human malignancies. 35,36 Recently, researchers have begun to assess anti-PCSK9 vaccines against breast cancer and melanoma in mice, 34,37 and a previous study reported that a nano liposomal anti-PCSK9 vaccine has potential anti-tumor effect in colorectal cancer. 14 This study directly linked PCSK9 with the development and progression of mouse adenomas and adenocarcinomas in transgenic mice, supporting previous studies which examined an anti-PCSK9 vaccine against colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PCSK9 has multiple biological functions, including regulation of cell apoptosis and the tissue inflammation response, in addition to regulating blood lipid in vivo. 30,31 The inhibition of PCSK9 induced the apoptosis of the lung cancer cells, A549, and the glioma cells, U251, 32,33 prevented liver metastasis in mice with melanoma, 34 and prolonged the survival of BALB/c mice inoculated with the colon cancer cells, CT26. 14 Over the past 10 years, a considerable amount of literature has accumulated on the role of PCSK9 in hypercholesterolemia and human malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this reveals that the inhibition of PCSK9 by vaccination had no side effects on the breast tumor endpoint and that it could improve breast cancer behavior [ 152 ]. On the other hand, vaccination with L-IFPTA + vaccine in mice bearing melanoma did not show any effect on tumor growth nor the survival of tumor-bearing mice [ 153 ]. Here again, the same peptide-based vaccine only bound 50% of circulating mouse PCSK9.…”
Section: Pcsk9 Targeting As a Potential Anti-cancer Approachmentioning
confidence: 99%
“…Proprotein convertase subtilisin kexin type 9 (PCSK9) is a major regulator of cholesterol homeostasis via binding and downregulating low-density lipoprotein receptor (LDLR) [ 21 25 ]. PCSK9 displays oncogenic actions in cancer [ 26 ], including gastric cancer [ 27 ], esophageal cancer [ 28 ], prostate cancer [ 29 31 ], breast cancer [ 32 ], ovarian cancer [ 33 ], lung cancer [ 34 37 ], hepatocellular carcinoma [ 38 , 39 ], and melanoma [ 40 , 41 ]. While accumulative evidence reveals a general action of PCSK9 in facilitating tumorigenesis, the specific association of PCSK9’s role in regulating lipid metabolism and its oncogenic potential remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the strong evidence for PCSK9’s oncogenic involvement, it is surprising that PCSK9 vaccine has no impact on melanoma and only modestly reduces breast cancer growth in murine models [ 32 , 40 ]. This may be related to the relative inefficiencies of the reported vaccines to completely block PCSK9 activity.…”
Section: Introductionmentioning
confidence: 99%